2022
DOI: 10.1177/15569845221106939
|View full text |Cite
|
Sign up to set email alerts
|

Totally Endoscopic Robot-Assisted Aortic Valve Replacement and Complex Mitral Valve Repair: The Lateral Approach

Abstract: A 76-year-old male patient was referred to our institution with moderate-to-severe aortic and mitral insufficiency. The patient underwent totally endoscopic robot-assisted aortic valve replacement and mitral valve repair. In this article, we present our lateral approach to the robotic double valve surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…5,6 Wong et al reported simultaneous surgery for AV replacement and MV repair via a lateral approach. 7 They stressed the importance of the lateral approach for the same reason that we shifted the camera port lateral and cranial to the standard position, which is used in our standard robotic MV surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Wong et al reported simultaneous surgery for AV replacement and MV repair via a lateral approach. 7 They stressed the importance of the lateral approach for the same reason that we shifted the camera port lateral and cranial to the standard position, which is used in our standard robotic MV surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our methods for robotic port placement and percutaneous cannulation were previously described in detail. 10,11 We routinely preclose the vessels by using 2 sets of Perclose ProGlide percutaneous suture (Abbott Laboratories, Chicago, IL, USA) each at 2 and 10 o’clock positions on the vessel before giving heparin. Once protamine administration is completed, an 8 Fr Angio-Seal (Terumo Medical Corporation, Tokyo, Japan) is placed for additional hemostasis.…”
Section: Robotic Port Placement Peripheral Cannulation and Intraclude...mentioning
confidence: 99%